Strengthening surgical healthcare research capacity in sub-Saharan Africa: impact of a research training programme in Nigeria - Ameh, Emmanuel A.; Seyi-Olajide, Justina O.; Ameh, Nkeiruka; Michael, Afieharo; Abdullahi, Mohammed AS; Aria, Oti Nimi; Obi, Nkeiruka; Chukwu, Isaac (Frontiers in Medicine, 2024)
Background Limited research capacity has contributed to the lack of high-quality research from low-and middle-income countries. This is compounded by limited research training opportunities. Research capacity scale-up training was deployed as part of the implementation of the National Surgical, Obstetrics, Anaesthesia, and Nursing Plan for Nigeria. We report the impact of this locally contextualized efforts to scale up research capacity in sub-Saharan Africa. Methods This is an evaluation of the training of 65 participants in research, grant writing and manuscript writing and publication. Pre- and post-training surveys using a 5-point Likert scale and open-ended questions were administered to evaluate the impact of the programme. Results There were 39 (60%) males and 26 (40%) females aged 26–62 years (median 42 years). Thirty-nine (60%) participants had previous training in research, but only 12 (18.5%) had previously received grant writing training, and 17 (26.2%) had previously received manuscript writing and publishing training. Following training, 45 (70.3%) participants agreed that the training was relevant. The research, grant writing and manuscript writing, and publication components of the training were rated high by the participants (45–59, 70.3–92.2%). However, 41.2% felt that there was not enough time, and 32.4% felt that the training was too comprehensive. Nearly all the participants agreed that the training had improved their skills in research, grant writing and manuscript writing and publication, and more than two-thirds subsequently engaged in informal mentoring of others. Overall, participants achieved success in designing their own research projects and publishing manuscripts and grants. Three (4.6%) of the participants had gone on to become faculty for the research training programme. The three top barriers encountered following training were time constraints (67.3%), lack of funding (36.5%) and not being able to find research collaborators (25%). Conclusion Outcome of this training programme is encouraging and highlights the feasibility and potential impact of deploying such programmes in low and middle income countries (LMICs). Despite the positive outcomes, barriers including time constraints, funding limitations, and difficulties in finding research collaborators remain to be addressed. Such training programmes need to be supported to strengthen the research capacity in this and similar settings.